Musykilat Ta’allum An-Nahw Li Thullaabi As-Shaf As-Saadis bi Kulliyati Al-Mu’allimiina Al-Islaamiyyah bi Ma’hadi Daari As-Salaami Gontor Li At-Tarbiyah Al-Islaamiyyah Al-Hadiitsah Al-Aam Ad-Diraasii 1440-1441 - Fairuz Subakir Ahmad; Alfy Mamduh Nuruddin (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2021)
AbstractDarussalam Gontor Modern Institution is one of the Islamic education institutions in Indonesia which implements a teaching curriculum with Arabic and English as the language of instruction. Students can improve their language skills.   One of these branches of knowledge is Nahwu. Nahwu  is lessons that play an important role in language improvement, not only that good mastery, Nahwu   can affect student learning achievement, because in Gontor, some of the lessons use Arabic, both the language of instruction or the language in the subject matter itself. However, the phenomenon is the number of students who have difficulty learning Nahwu, especially students in grade VI. Therefore, the researchers tried to uncover their problems in learning Nahwu.This research used qualitative research methods, to achieve these objectives, the researcher used 3 methods,   the observation  , the interview  , and the written record method. The data analysis used refers to Miles Hubberman,   data reduction, data display, and data analysis, as well as conclusions and verification.The analysis  found that: (1)there are some  Problems in learning Nahwu for grade VI students,  : (a) Lack of students' skills in receiving explanations about Nahwu (b) Absence or lack of interest in learning Nahwu (c) Absence of motives for students in learning Nahwu (d) Lack of attention from students in understanding Nahwu rules (e) Lack of students in practicing "i'rob" (f) The language used in the book is too difficult for students (g) Explanation of teachers that students do not understand.            From this   research, the researcher hopes that all teachers, especially Nahwu teachers, will make serious efforts in guiding students to learn Nahwu, so that they can uncover their difficulties.for  the next researchers for more detail and deeper learning about Nahwu. We hope that we can complete the current shortcomings to be better and useful.Keywords: Problems, Learning Nahwu, Class Six.